Refining of associated petroleum gases C3-C4 into liquid hydrocarbons on zeolite-containing catalyst base - Erofeev V. I. Vladimir Ivanovich (Section 1. Chemical engineering and "Green technology", 2012)
The following article describes research in acid and catalyst properties of zeolite MFI catalysts, modified zinc, gallium, copper, wolframite and other metals. Modified additives of zinc, gallium and copper in zeolites, significantly increase catalyst activation and selective formation of liquid hydrocarbons fromassociated petroleum gases (APG) C3-C4. Characteristic features of APG - C3-C4 conversion process on ZCC base were determined.